Solution of Dirac dynamic system by Laplace transform on time scales in quantum physics - Yilmaz, Emrah; Aydin, Elif; Goktas, Sertac (Univ Nis, Fac Sci Math, 2024)
In this study, we solve a Dirac dynamic system on time scale with constant graininess by using Laplace transform which converts differential equations into algebraic equations and convolution into multiplication. It has many applications in science and engineering. Furthermore, we give some numerical examples for special time scales related to the Laplace transform.
Keywords: Time scales; Dirac system; Laplace transform